Myocardial ischemia due to a recanalized chronic coronary thrombus: Angiographic and optical coherence tomography imaging insights. Issue 8 (24th June 2020) - Sacchetta, Giorgio; Scalise, Renato Francesco Maria; Garcia Ruiz, Victoria; Barrano, Giombattista; Garro, Nadia; Costa, Francesco; Contarini, Marco
Abstract: Chronic organized thrombus as a result of prior untreated myocardial infarction can determine myocardial ischemia. This entity appears as an angiographically irregular and hazy image; optical coherence tomography is useful to evaluate these ambiguous lesions and guide interventional treatment. Abstract : Chronic organized thrombus as a result of prior untreated myocardial infarction can determine myocardial ischemia. This entity appears as an angiographically irregular and hazy image; optical coherence tomography is useful to evaluate these ambiguous lesions and guide interventional treatment.